Comparison of the effect of two therapeutic exercises on the inflammatory and physiological conditions and complications of diabetic neuropathy in female patients - Nadi M (Dove Medical Press, 2019)
Maryam Nadi,1 Effat Bambaeichi,2 Seyyed Mohammad Marandi21Exercise Physiology, University of Isfahan, Isfahan, Iran; 2Faculty of Sport Sciences Department, University of Isfahan, Isfahan, IranCorrespondence: Effat BambaeichiFaculty of Sport Sciences Department, University of Isfahan, Azadi Square, Isfahan 8174673441, IranTel +98 913 205 0472Email e.bambaeichi@yahoo.comIntroduction and aim: The purpose of this study was to compare the effect of 12 weeks of low-intensity resistance training and exercises for peripheral neuropathy (EPN) on the inflammatory and physiological conditions, balance, and complications of diabetic neuropathy in female patients.Materials and methods: 45 women with mild to moderate diabetic neuropathy and an average age of 55.46±3.06 years voluntarily participated in the study. They were randomly assigned to either control (n=15), resistance (n=15), and EPN (n=15) groups. Both experimental groups were trained for 12 weeks (three sessions per week). EPN group did peripheral neuropathic exercises (12 lower extremity movements), and the resistance group performed their exercises with a 30% repetition maximum. During the intervention period, the control group only performed their daily activities. Blood samples were taken in both pre-test and post-test to investigate the levels of Tumor necrosis-α (TNF-α), Interleukin-10 (IL-10), C Reactive Protein (CRP), fast blood glucose (FBG) and Glycated hemoglobin (HbA1c). Complications of diabetic neuropathy were measured using the Michigan questionnaire and the Monofilament 10 g. In order to measure the balance, De Morton mobility index (DEMMI) was used.Results: The statistical analyses showed a significant decrease of FBG and HbA1c in the two experimental groups, as compared to the control group. TNF-α and CRP levels were decreased in both EPN and resistance groups, as compared to the control group. The observed increase in the serum IL-10 levels of the two experimental groups was not, however, significant, as shown in intra-group and inter-group comparisons. On the other hand, the two complications of pain and tingling in the lower limb extremities were improved in both experimental groups (p<0.05). However, the numbness complication showed no significant change (p=0.10). Static and dynamic balance was improved in the EPN group as well (p<0.05).Conclusion: Since EPN exercises, in contrast to resistance exercises, are focused on the lower limb extremities and designed for diabetic neuropathy patients, they can improve the imbalance, pain and tingling, by significantly reducing TNF-α and CRP and improving the physiological conditions.Keywords: TNF-α, IL-10, CRP and diabetic neuropathy exercises